Design of 3-D multilayer ferrite-loaded frequency-selective rasorbers with wide absorption bands - Deng, Tianwei (2021)
A multilayer structure and magnetic ferrite material are employed to expand the absorption bandwidth of 3-D frequency-selective rasorber (FSR). Resonant-like ferrite is used to realize the magnetic loss with high selectivity of absorption over a wide frequency band, while the multilayer structure is proposed to achieve multiple absorption peaks at designated frequencies. Combining the loaded ferrite material with multilayer structure can realize wide absorption bands. Equivalent circuit models are utilized to understand the operating mechanism of the described 3-D structure and to guide the design of multilayer structure with selected ferrite materials. Two broadband 3-D FSRs are designed, fabricated, and measured. Both designs achieve the sextuple bandwidth ratio with reflectivity less than-10 dB, and the absorption band with a bandwidth ratio of >2.6:1 can be achieved at either lower or upper absorption band, respectively.